Khunrath in Context : An Alchemist in the Amphitheatre of Eternal Wisdom - Karpenko, Vladimir, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
The German physician, alchemist, kabbalist, and theosopher Heinrich Khunrath (ca. 1560-1605) is one of the most remarkable figures in the intellectual history of the Renaissance. His work, combining text and images in a new way, is a fusion of the contemporary currents of thought in which alchemy went hand-in-hand with philosophy and Lutheran heterodox theology. As a follower of Paracelsus, Khunrath was in search of both the secrets of nature and and the knowledge of God -- the "theosophy". This See Less